Interpreting 'the social': Exploring processes of social sustainability in Danish nonprofit housing. (August 2019) - Langergaard, Luise L
The article aims at analyzing and discussing how "the social" is perceived in processes of social sustainability within the context of the nonprofit housing sector in Denmark. The investigation takes as point of departure a specific renovation project, which exemplifies an attempt to bring social sustainability to the core of the process. As such, the study analyses the process by distilling various understandings of "the social" appearing in the project and herein the different types of participation that these understandings relate to. The analysis demonstrates that working with social sustainability and the aims and ideals connected to it is not straight forward, since "social sustainability" is not a tangible target, but rather something which is reinterpreted and subject to changing perceptions along the process. The dynamic and changing character of "sociality" suggests that social sustainability requires a focus on the platforms and on-going processes and interactions which continuously constitute the social life in a neighborhood and the relations between the residents. In this manner the article adds to empirical knowledge about processes organized to strengthen social sustainability in urban environments and contributes theoretically with a nuanced understanding of what "social" denotes in the context of sustainable development.